Long Noncoding RNAs, Chromatin, and Development - Daniel P. Caley; Ryan C. Pink; Daniel Trujillano; David R. F. Carter (The Scientific World Journal)
The way in which the genome of a multicellular organism can orchestrate the differentiation of trillions of cells and many organs, all from a single fertilized egg, is the subject of intense study. Different cell types can be defined by the networks of genes they express. This differential expression is regulated at the epigenetic level by chromatin modifications, such as DNA and histone methylation, which interact with structural and enzymatic proteins, resulting in the activation or silencing of any given gene. While detailed mechanisms are emerging on the role of different chromatin modifications and how these functions are effected at the molecular level, it is still unclear how their deposition across the epigenomic landscape is regulated in different cells. A raft of recent evidence is accumulating that implicates long noncoding RNAs (lncRNAs) in these processes. Most genomes studied to date undergo widespread transcription, the majority of which is not translated into proteins. In this review, we will describe recent work suggesting that lncRNAs are more than transcriptional "noise", but instead play a functional role by acting as tethers and guides to bind proteins responsible for modifying chromatin and mediating their deposition at specific genomic locations. We suggest that lncRNAs are at the heart of developmental regulation, determining the epigenetic status and transcriptional network in any given cell type, and that they provide a means to integrate external differentiation cues with dynamic nuclear responses through the regulation of a metastable epigenome. Better characterization of the lncRNA-protein "interactome" may eventually lead to a new molecular toolkit, allowing researchers and clinicians to modulate the genome at the epigenetic level to treat conditions such as cancer.